NFR catalogues for RFID middleware - Torres, Renato Cristiano (2014)
Non-functional requirements (NFR) are related to the user satisfaction about the quality attributes of the information system. In some cases these requirements are ignored or implemented by the end of the project in a chaotic way. It happens because, in many cases, the user does not have enough contact with the information system to solve these requirements, such as nonfunctional requirements for Radio-Frequency Identification (RFID) middleware. This study presents the preparation of non-functional requirements catalogues for RFID middleware supported by Non-Functional Requirements Framework (NFR-Framework). Two case studies were performed to evaluate the Requirements Engineering process in the creation of the NFR catalogues and the effectiveness of the reuse of the catalogues. As a result, a set of non-functional requirements are presented and organized into catalogues that work as the foundation for RFID system developers in the identification and validation of non-functional requirements for RFID middleware in information systems context.